Application of Arjuna (Terminalia arjuna) seed biochar in hybrid treatment system for the bioremediation of Congo red dye - Goswami M.; Chaturvedi P.; Kumar Sonwani R.; Dutta Gupta A.; Rani Singhania R.; Shekher Giri B.; Nath Rai B.; Singh H.; Yadav S.; Sharan Singh R. (My University, 2025)
In the present study, a hybrid treatment system (biological and ozonation) was developed and used in the decolorization of Congo red (CR) dye. The biological treatment was performed in packed bed bioreactor (PBBR) containing Arjuna (Terminalia Arjuna) seeds biochar immobilized with Providencia stuartii, whereas ozonation was carried out in an ozone reactor. The process variables such as temperature, process time, and inoculum size were optimized and found to be 30 °C, 2 48 h, and 3 × 105 CFU/mL, respectively with 92.0 ± 5.0% of dye decolorization. Furthermore, biologically treated effluent was subject to ozone treatment for the decolorization of the remaining CR dye. The hybrid approach reveals almost complete decolorization of Congo red (CR) dye. The kinetic study of microbial growth was examined by Monod model. In addition, the cost analysis estimation for the removal of CR dye was done, and removal per liter was found to be economic. © 2020